Pengaruh Model Pembelajaran Discovery Learning terhadap Hasil Belajar Seni Rupa Kelas VIII di SMPN 3 Lengayang - Ningsi, Nori Gusdia; Yahya, Yahya (Lembaga Yasin AlSys, 2025)
The purpose of this study is to find out how the learning outcomes of fine arts students in grade VIII at SMPN 3 Lengayang are influenced by the discovey learning model. Researchers conducted